Kepribadian Berbasis Imani Perspektif Psikologi Islam - Asep Suraya Maulana (Jurnal Hikmatuna, 2019)
This article is a type qualitative through books or literature review and reality that happened, as in the news presented by both the print and electronic media has never been separated from discussing various incidents such as, violence, crime, crime, injustice, abuse, rape, violation of rights, riots, murder self, drug use, abortion and so on. Human attitudes that have always committed immorality. Indeed, Islam has always taught good values, so that human beings have an immoral personality that always applies the Ashraful karimah. Humans in the view of Islamic Psychology has a set of potential, disposition, and unique character. That potency at least includes faith, monotheism, Islam, salvation, sincerity, purity, the tendency to accept truth and goodness, and other good qualities, as; shindig, Amanah, tabligh, dan Katonah.